Strengthening of Metallurgical Equipment Parts by Plasma Surfacing in Nitrogen Atmosphere; Metallurgist; Vol. 65, iss. 11-12 - Malushin N. N. Nikolay Nikolaevich; Martyushev N. V. Nikita Vladimirovich; Valuev D. V. Denis Viktorovich; Karlina A. I. Antonina Igorevna; Kovalev A. P. Andrey Petrovich; Gizatulin R. A. Rinat Akramovich (2022, 2022)
Title screen